2019
DOI: 10.1080/21655979.2019.1682108
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering tools for the production of pharmaceuticals: current perspective and future outlook

Abstract: The bioengineering tools have significant advantages through less time-consuming and utilized as a promising stage for the production of pharmaceutical bioproducts under the single platform. This review highlighted the advantages and current improvement in the plant, animal and microbial bioengineering tools and outlines feasible approaches by biological and process's bioengineering levels for advancing the economic feasibility of pharmaceutical's production. The critical analysis results revealed that system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 128 publications
(130 reference statements)
0
19
0
Order By: Relevance
“…The development of sophisticated molecular approaches in conjunction with computational regulations has resulted in a decline in the sequencing of aggregate genome DNA and several opportunities related to marine microbial exploration ( Figure 5). As a result, an entire era of metagenomic sequencing has contributed to more in-depth considerations of representing a wider range of species from varying tests [63][64][65][66]. Li et al [67] showed that metagenomicsbased population analyses can provide both community and valuable information without an upgrade slant.…”
Section: Microbial Metagenomicsmentioning
confidence: 99%
“…The development of sophisticated molecular approaches in conjunction with computational regulations has resulted in a decline in the sequencing of aggregate genome DNA and several opportunities related to marine microbial exploration ( Figure 5). As a result, an entire era of metagenomic sequencing has contributed to more in-depth considerations of representing a wider range of species from varying tests [63][64][65][66]. Li et al [67] showed that metagenomicsbased population analyses can provide both community and valuable information without an upgrade slant.…”
Section: Microbial Metagenomicsmentioning
confidence: 99%
“…Owing to the increasing global demand for anti-cancer drugs, the global market for dendrobine is increasing rapidly and is expected to cross the outer limit of other drugs. Thus, the demand for dendrobine will continue to increase (Li et al, 2017;Sarsaiya et al, 2019c). However, dendrobine is an expensive drug and, therefore, not easily accessible to many people worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the quality assurance, it is necessary to demonstrate batch-by-batch reproducibility in bioprocesses. The production of anti-SARS-CoV-2 mAbs in CHO cells can be seen as a feasible strategy for implementation on an industrial scale in conjunction with high-density cultures [ 272 ], single-use technologies [ 267 ], design/selection techniques for highly productive clones [ 264 , 281 ], and bioprocess optimization [ 266 ]. To achieve this, it is necessary that companies with large biotechnological developments provide insights to the bio-pharmacological industry to combat this global pandemic.…”
Section: Remarks On the Production Of Mabs For Covid-19 Treatmentmentioning
confidence: 99%